Morphometric characteristics of tropical shallow reservoir used for aquaculture and agriculture in the mexican plateau - Aldama, G R; Ponce-Palafox, J T; Cruz, LFG; Hernández, D O; Diaz, J A; Arredondo-Figueroa, J L (Revista Bio Ciencias, 2013)
Morphometric characteristics of a tropical shallow reservoir situated in the Southern Mexican Highlands were studied. Seventeen morphometric parameters were measured. Results of the morphometric parameters showed that this reservoir presented a soft and roughness bottom, with an ellipsoid form and a concave depression that allow the mix up of water and sediments, causing turbidity and broken thermal gradients; its slight slopes allowed the colonization of submerged macrophyte and halophyteplants and they improve the incidence of sunlight on water surface increasing evaporation and primary productivity. Tropical shallow reservoirs have fluctuations in area and volume according to the amount of rainfall, the effectof evaporation, the temperature levels, lost of volume due to irrigation, and other causes.